Development of an air conditioning system with individual regulation of temperature and air flow rate in a compartment of a passenger car - G. M. Stoyakin; A. V. Kostin; S. N. Naumenko (Вестник Научно-исследовательского института железнодорожного транспорта)
Maintaining optimal parameters of the microclimate in the car along the route is the most important requirement for the passenger’s travel. In the 1st class passenger cars, maintaining optimal microclimate parameters is achieved through the operation of the air conditioning system, which provides individual regulation of the air temperature in each compartment. Individual air temperature control systems used in air conditioning systems are divided into two groups: active and passive.The article proposes for consideration a combined active-passive system with a separate air supply with a lower and higher temperature compared to the temperature maintained in the compartment and the installation of individual induction terminals, which makes it possible to increase the efficiency of individual regulation of air parameters in the compartment.To assess the uniformity of temperature distribution and air flow rate over the car volume with the proposed control scheme, a three-dimensional modeling of the distribution of these parameters in the compartment was carried out on the basis of Autodesk CFD software.The given simulation results indicate the uniformity of temperature and air flow rate distribution over the compartment volume, which makes it possible to characterize the proposed system as sufficiently energy efficient, easy to operate and reliable in operation.